THE GOVERNMENT’S ROLE IN PROTECTING INDONESIAN MIGRANT WORKERS IN SAUDI ARABIA DURING THE JOKO WIDODO ADMINISTRASION - Bachtiar, Farahdiba Rahma; Hidaya, Razinatul (Hasanuddin Journal of Strategic and International Studies (HJSIS), 2024)
Saudi Arabia is one of the largest destination countries for Indonesian immigrant workers, where the majority are women. Unfortunately, most of them are also victims of physical torture, sexual violence and rational discrimination. This resulted in many cases emerging as a result of this torture. However, the policies during the Jokowi era are considered quite progressive compared to the policies for protecting migrant workers during the Susilo Bambang Yudhoyono (SBY) period with the presence of special laws, not just Presidential Regulations as were issued during the SBY era. How and why the government plays such a significant role is the main study in this research. This research uses a qualitative approach with a library study type of research. The results found were that the government during Jokowi's leadership played a big role in protecting the rights of Indonesian migrant workers, especially in Saudi Arabia. This role is reflected in the government's responsibility in various policies which make Jokowi's policies considered pro People Diplomacy. Through the 2015-2019 Medium Term Development Plan, for example and supported by Nawa Cita, during the Jokowi government, Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers was issued as the highest legal umbrella which was then also followed by other policies such as bilateral cooperation and placement systems. channel (SPSK) or One Channel System. The Jokowi government's policy is based on two reasons. First, the fact that immigrant workers in Saudi Arabia contribute the largest remittance of all migrant workers in various countries, beating Malaysia (Kompas, 2023). Second, migrant workers are a potential profession to meet Indonesia's demographic bonus target in the future. Therefore, this research sees that the government's role in protecting migrant workers has been very good during the Jokowi administration. It's just that the issue of Indonesian migrant workers requires commitment from other actors who also play a very important role, such as distribution companies or providers of migrant workers.